Maintenance of organellar protein homeostasis by ER-associated degradation and related mechanisms - Lemberg, Marius; Stříšovský, Kvido (Molecular cell, 2021)
Protein homeostasis mechanisms are fundamentally important to match cellular needs and to counteract stress conditions. A fundamental challenge is to understand how defective proteins are recognized and extracted from cellular organelles to be degraded in the cytoplasm. The endoplasmic reticulum (ER)-associated degradation (ERAD) pathway is the best-understood organellar protein quality control system. Here, we review new insights into the mechanism of recognition and retrotranslocation of client proteins in ERAD. In addition to the membrane-integral ERAD E3 ubiquitin ligases, we highlight one protein family that is remarkably often involved in various aspects of membrane protein quality control and protein dislocation: the rhomboid superfamily, which includes derlins and intramembrane serine proteases. Rhomboid-like proteins have been found to control protein homeostasis in the ER, but also in other eukaryotic organelles and in bacteria, pointing toward conserved principles of membrane protein quality control across organelles and evolution.